Author Correction: Characterising the unity and diversity of executive functions in a within-subject fMRI study (Scientific Reports, (2022), 12, 1, (8182), 10.1038/s41598-022-11433-z) - Saylık, Rahmi; Williams, Adrian L.; Murphy, R.A.; Szameitat, A.J. (Nature Research, 2022)
The original version of this Article contained an error in the Data Availability section where “The stimuli and processed data files will be available available at: figshare.” now reads: “The stimuli and processed data files are available at https:// doi. org/ 10. 6084/ m9. figsh are. 19780 264.” The original Article has been corrected. © The Author(s) 2022.
Keywords: erratum